2015
DOI: 10.1007/s00706-015-1515-7
|View full text |Cite
|
Sign up to set email alerts
|

2-Amino-1,3,5-triazine chemistry: hydrogen-bond networks, Takemoto thiourea catalyst analogs, and olfactory mapping of a sweet-smelling triazine

Abstract: The chemistry of 4,6-dialkyl-2-amino-1,3,5-triazines with bulky alkyl substituents was investigated and their use as building blocks for preparing chiral thiourea organocatalysts explored. Reaction of ammonia with 4,6-di-tert-butyl-2-chloro-1,3,5-triazine gave 4,6-di-tert-butyl-1,3,5-triazin-2-amine which formed extended hydrogenbond networks in the solid state according to X-ray crystallography. Selected heterocyclic amines were converted to isothiocyanates, and the latter reacted with (S,S)-2-(dimethylamino)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The same measurements were also carried out on 2-AT at neutral pH in buffer solution and the corresponding TA spectra are illustrated in Figure e−f while the dynamics are shown in Figure c for comparison. Previous study reported the p K a value of 2-AT should be 2.9 and 14.9, suggesting that 2-AT is in neutral form in buffer solution (pH = 7.4) and the interference from tautomer should not exist in our study. Again, the TA signals build up within the instrument resolution just like 5-AC and 2,4-DT.…”
Section: Resultsmentioning
confidence: 50%
“…The same measurements were also carried out on 2-AT at neutral pH in buffer solution and the corresponding TA spectra are illustrated in Figure e−f while the dynamics are shown in Figure c for comparison. Previous study reported the p K a value of 2-AT should be 2.9 and 14.9, suggesting that 2-AT is in neutral form in buffer solution (pH = 7.4) and the interference from tautomer should not exist in our study. Again, the TA signals build up within the instrument resolution just like 5-AC and 2,4-DT.…”
Section: Resultsmentioning
confidence: 50%
“…Because 1,3,5-triazin-2-amines exhibit various biological and medicinal activities, various methods for the synthesis of diverse 1,3,5-triazin-2-amines have been developed . However, the direct synthesis of 1,3,5-triazin-2-amines from readily available substrates is rare.…”
Section: Introductionmentioning
confidence: 99%